Empowerment of Santri at Padepokan Siti Dhumillah, Bogor: A Productivity Improvement Program Through Processing Farm Products as Agribusiness and Business Education. - Ahmad Maulidizen; Risman Nugraha; Muhammad Alfriandra Hedza Ramadhan; Niken Chaerunisa; Fadel Hafidh Isman; Adiva Aura Assyari; Muhammad Zailani Iman (SocietalServe: Journal of Community Engagement and Services, 2024)
This community service program aims to enhance the productivity of students (santri) at Padepokan Siti Dhumillah, Bogor, by leveraging agribusiness and business education approaches. Utilizing local agricultural produce such as chili peppers and tomatoes, the program fosters value-added product innovation through the production of sambal under the brand "Nyambel Neh." It is designed to integrate education on technology, online marketing, and business operations, enabling students to acquire not only technical skills but also a comprehensive understanding of agribusiness opportunities. The implementation method involves dividing tasks into specific divisions, including equipment, production, and marketing, supported by mentors providing direct education. Program stages include business and technology education, transforming raw materials into market-ready products, and marketing these products through both online and offline platforms. Outcomes from the program include the creation of three modernly packaged sambal variants, the development of visionary and creative student personalities, and the increased economic sustainability potential of the Padepokan through business diversification. This program aspires to become a model for student empowerment, focusing not only on economic benefits but also on building human resource capacity to compete in the future. By optimizing technology and adopting practice-based learning, students are expected to independently create new business opportunities centered around agribusiness.